Período de floração e viabilidade do pólen das cultivares de oliveira Arbequina e Koroneiki, em Bagé/RS. - Cappellaro, Thais Helena (2010)
The olive tree (Olea europaea L.) is a member of the Oleaceae family which includes about 35 species of the genera Olea. All native and cultivated olive trees belong to the Olea europaea species. Researches with olive trees have recently been restarted in Brazil, and that is why there are little informations about this crop in this country. For this reason, it is important to develop studies about bloom period and pollen viability on olive cultivars such as Arbequina and Koroneiki. The objectives for this study were: to define the blooming period; to compare methods for pollen viability evaluation; to evaluate the effects of boric acid added to the medium on pollen germination; and to evaluate the viability of 12 months cold stored pollen, for these two cultivars. The data of bloom period for the two cultivars were obtained from 5 year-old trees grown in an orchard located in Bagé-RS, through observations made during the blooming period in the years of 2008 and 2009. Pollen viability of these two cultivars, were evaluated through three experiments in a laboratory. The first experiment were compared three methods of pollen viability evaluation: colorimetric method; in vitro germination; and in vivo germination. The variable was the pollen viability expressed as percentage (colorimetric, identified only by staining of pollen in vitro and in vivo, the percentage of pollen germinated). The second experiment were compared the effects on pollen germination of boric acid concentrations (0; 25; 50; 75; 100; or 125 mg.L-1) added to the germination medium containing agar 1% plus sucrose 15%. In a third experiment, pollens of both cultivars placed inside desiccators containing silica-gel and kept at -16°C for 12 months, were evaluated on their germination viability. It was observed that: In 2008, both cultivars started bloom on October 16th, and end of blooming on November 11th, while in 2009 the starting of bloom was on October 20th and the end of blooming on November 3rd for both cultivars. Therefore the blooming period was shorter in 2009 (21 days) as compared to that of 2008 (27 days); the colorimetric method make possible to identify highest percentages of viable pollen grains, however this method may overestimate pollen viability; the addition of boric acid to the media do not affect pollen germination; and pollen of both cultivars decreased their viability when stored in desiccators at -16°C during 12 months.